(untitled) (American Journal of Islam and Society, 1991)
Introduction The purpose of this paper is to delineate the basic elements involved in the concept of the Islamic state and to clarify the basis and scope of political power. More specifically, discussions will focus on the purpose of the Islamic state, the source of political legitimacy, and the scope of state power. I will contend that a clear distinction should be made between the role and purpose of the state and those of the ummah, for only through the separation of the responsibilities and objectives of the two can the injunctions of the Shari‘ah and the principles of revelation be properly observed. Historical Background Although the word “state” (dawlah) was first used in the Qur’an, almost six centuries had to elapse before the word was given its first technical definition by Muslim scholars. The word dawlah was mentioned once in the Qur’an (in 59:7) in connection with the distribution of the fay’ (the property Muslims appropriated from the Banu al Nadr upon the latter‘s expulsion from Madinah). The Qur’an justified this departure from the usual practice of dividing the spoils among the fighters by referring to the divine intention of preventing the circulation of wealth among a small group within the society? Up until the late fifth century, one could hardly find any reference to the state in Muslim literature, or in Western literature for that matter. Other terms such as al amsar or dar al Islam were employed whenever a reference was made to the territories under Muslim control. Alternatively, the state as a political body was identified by its political organs, i.e., al khilafah, ...